Estrategia metodológica para mejorar la destreza motriz en el lanzamiento del balón en el minibasquet en los niños de 6to año de educación general básica de la escuela Zoila María Astudillo de la ciudad de Loja, período 2012-2013 - Saritama Elizalde, Nora Mercedes (2015)
The referfente research the problem how to improve the driving dexterity in launching the ball at the kids minibasket 6th year of General Basic Education" Zoila Maria Astudillo" in the city of Loja, 2012-2013, as proposed School aim to design a methodological strategy to improve motor skills in launching the ball at the minibasket children in 6th year of school mentioned , for which we used for data collection technique survey of teachers and students respectively; Document analysis was applied to study the most appropriate methodological strategy for the development of the skill in question. In the information processing scientific, analytic, synthetic, descriptive, inductive-deductive method was used. The main results of the research found that teachers do not possess concerning theoretical and methodological associated with motor skill in launching the ball at the minibasket and also not implemented a process of development to that end, no teachers have the methods, procedures and suitable for the development of such skill techniques, so was prepared, presented and implemented an alternative proposal, it gave excellent results, which improved the development of motor skills. Despite the drawbacks such as lack of resources for physical and sports classes minibasket, the skill of ball release was developed, which contributes significantly to the quality of education. Since there is a close relationship between the approaches and the development of skills .